2021
DOI: 10.3390/ijms22179563
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of a Donepezil-Huprine Hybrid against the β-Amyloid (1-42) Effect on Human Erythrocytes

Abstract: Aβ(1-42) peptide is a neurotoxic agent strongly associated with the etiology of Alzheimer’s disease (AD). Current treatments are still of very low effectiveness, and deaths from AD are increasing worldwide. Huprine-derived molecules have a high affinity towards the enzyme acetylcholinesterase (AChE), act as potent Aβ(1-42) peptide aggregation inhibitors, and improve the behavior of experimental animals. AVCRI104P4 is a multitarget donepezil-huprine hybrid that improves short-term memory in a mouse model of AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…These compounds have been found to exhibit a remarkable protective activity against the deleterious effects of the Aβ(1–42) peptide on the natural and synthetic membrane models. AVCRI104P4, a donepezil-huprine hybrid with multitarget functions, has been shown to ameliorate short-term memory deficits in a mouse model of Alzheimer’s disease and exert protective effects in transgenic Caenorhabditis elegans expressing the Aβ(1–42) peptide . The study further elucidates the effects of AVCRI104P4 on natural membrane models, demonstrating a protective effect against the toxicity induced by the Aβ(1–42) peptide.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…These compounds have been found to exhibit a remarkable protective activity against the deleterious effects of the Aβ(1–42) peptide on the natural and synthetic membrane models. AVCRI104P4, a donepezil-huprine hybrid with multitarget functions, has been shown to ameliorate short-term memory deficits in a mouse model of Alzheimer’s disease and exert protective effects in transgenic Caenorhabditis elegans expressing the Aβ(1–42) peptide . The study further elucidates the effects of AVCRI104P4 on natural membrane models, demonstrating a protective effect against the toxicity induced by the Aβ(1–42) peptide.…”
mentioning
confidence: 69%
“…AVCRI104P4, a donepezil-huprine hybrid with multitarget functions, has been shown to ameliorate short-term memory deficits in a mouse model of Alzheimer's disease and exert protective effects in transgenic Caenorhabditis elegans expressing the Aβ(1−42) peptide. 4 The study further elucidates the effects of AVCRI104P4 on natural membrane models, demonstrating a protective effect against the toxicity induced by the Aβ(1−42) peptide. On the other hand, recent studies have been demonstrated that RHE-HUP, a rhein-huprine hybrid, interacts predominantly with dimyristoylphosphatidylcholine (DMPC), a major component of the outer phospholipid monolayer of cell membranes (including neurons), and protects against the disruptive effect of the Aβ(1−42) peptide.…”
mentioning
confidence: 78%
“…Any alterations in the number and function of erythrocytes, or the decreased adherence to erythrocytes, may prevent amyloid-β from being transported and cleared in peripheral organs, eventually leading to amyloid-β accumulation in the brain. Recent studies also have found a significant association between amyloid-β and erythrocytes [ 268 , 269 ]. For instance, Taylor et al showed a new strategy in which immune complexes simultaneously capture amyloid-β and adhere it to erythrocytes via complement receptor 1 (CR1; CD35), promoting the rapid clearance of amyloid-β from the circulation and the brain [ 270 ].…”
Section: Amyloid-β Clearance In the Peripherymentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a progressive neurodegenerative disease characterized by diminished memory function, behavioral disorders, and cognitive impairments. The typical pathological features of AD are senile plaque formation by accumulation of amyloid beta (Aβ) and neurofibrillary tangles formation by Tau protein hyperphosphorylation. , Owing to the remarkable effectiveness of the treatment for Aβ accumulation in basic research, it is considered to be the most promising target for treating AD. However, many clinical studies have shown the limited efficacy of Aβ-targeted therapy in patients with AD .…”
Section: Introductionmentioning
confidence: 99%